2020
DOI: 10.1111/adb.12937
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent chronic intermittent toluene inhalation dynamically regulates the transcriptome and neuronal methylome within the rat medial prefrontal cortex

Abstract: Inhalants containing the volatile solvent toluene are misused to induce euphoria or intoxication. Inhalant abuse is most common during adolescence and can result in cognitive impairments during an important maturational period. Despite evidence suggesting that epigenetic modifications may underpin the cognitive effects of inhalants, no studies to date have thoroughly investigated toluene‐induced regulation of the transcriptome or discrete epigenetic modifications within the brain. To address this, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…However, it is difficult to exclude the impacts from benzene. As a single agent, exposure to toluene, even at low levels, has been found to change DNA methylation levels [ 254 , 255 , 256 ]. Hong et al showed that twenty-six genes are upregulated and hypomethylated, while 32 genes are downregulated and hypermethylated using in vivo samples [ 254 ]; changes in histone modifications (acetylation pattern of histones H3 and H4) [ 257 , 258 ] and microRNA expression are also observed [ 251 ].…”
Section: Epigenetic Effects Associated With Carcinogenic Chemicals From Gasolinementioning
confidence: 99%
“…However, it is difficult to exclude the impacts from benzene. As a single agent, exposure to toluene, even at low levels, has been found to change DNA methylation levels [ 254 , 255 , 256 ]. Hong et al showed that twenty-six genes are upregulated and hypomethylated, while 32 genes are downregulated and hypermethylated using in vivo samples [ 254 ]; changes in histone modifications (acetylation pattern of histones H3 and H4) [ 257 , 258 ] and microRNA expression are also observed [ 251 ].…”
Section: Epigenetic Effects Associated With Carcinogenic Chemicals From Gasolinementioning
confidence: 99%
“…Unfortunately, it is widely used in various commercial products such as paint and printing inks and numerous industrial processes such as petrol production (Cruz, Torres-Flores & Galván 2019). Acute and chronic exposure to toluene has been shown to induce neurologic changes in animals and humans (Armenta-reséndiz et al 2019;Braunscheidel et al 2019;Demir et al 2017;Dick et al 2021;Soares et al 2020;Werder et al 2019) leading to deteriorating effects on the central nervous system. There is currently no medication for neuroprotection after toluene exposure.…”
mentioning
confidence: 99%